AD⁺ a customized mental exercise therapy manipulative that promotes interaction, motor cognition, and mental stimulation to slow development of Alzheimer's disease in patients in the early to moderate stages - Ratilla, Daniel C.
Alzheimer's disease is an incurable and irreversible disease characterized by progressive mental deterioration. Mental exercise, motor exercise, and social interaction have been found to 'bolster the brain', and delay the disease's progression. With this, I designed a customize mental exercise therapy manipulative that promotes interaction, motor cognition, and mental stimulation to slow development of Alzheimer's disease in patients in the early to moderate stages. "Adding Value, Reducing Decline", AD⁺ makes therapy personal, offering deeper and more meaningful engagement to Alzheimer's disease patients.